2019
DOI: 10.1002/bies.201900091
|View full text |Cite
|
Sign up to set email alerts
|

DNA G‐Quadruplexes (G4s) Modulate Epigenetic (Re)Programming and Chromatin Remodeling

Abstract: Here, the emerging data on DNA G‐quadruplexes (G4s) as epigenetic modulators are reviewed and integrated. This concept has appeared and evolved substantially in recent years. First, persistent G4s (e.g., those stabilized by exogenous ligands) were linked to the loss of the histone code. More recently, transient G4s (i.e., those formed upon replication or transcription and unfolded rapidly by helicases) were implicated in CpG island methylation maintenance and de novo CpG methylation control. The most recent da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 122 publications
1
33
0
Order By: Relevance
“…As a further proof, AP-1 and SP1 were co-immunoprecipitated using anti-G4 primary antibody ( Figure 4D, lanes 2-3) and, vice versa, primary antibodies against SP1 and AP-1 co-immunoprecipitated the anti-G4 antibody added to the samples as marker of G4 regions ( Figure 4D, lanes 4-8), proof that these TFs interact with their binding sites in the presence of folded G4s (Figure 4D). These data indicate that TFs AP-1 and SP1 are strictly linked to G4s and suggest that G4s are exploited by cells to facilitate TF interaction with the DNA: this effect is reached by G4-mediated exposure of the binding region or altered DNA methylation state, as G4s were reported to prevent CpG island methylation, condition which is required for transcription initiation 3,14,27 . An alternative possibility is that TF binding to G4 regions stimulates G4 folding to maintain the underneath chromatin in a transcription permissive state.…”
Section: Analysis Of Accessible Chromatin Regions By Omni-atac-seqmentioning
confidence: 85%
See 1 more Smart Citation
“…As a further proof, AP-1 and SP1 were co-immunoprecipitated using anti-G4 primary antibody ( Figure 4D, lanes 2-3) and, vice versa, primary antibodies against SP1 and AP-1 co-immunoprecipitated the anti-G4 antibody added to the samples as marker of G4 regions ( Figure 4D, lanes 4-8), proof that these TFs interact with their binding sites in the presence of folded G4s (Figure 4D). These data indicate that TFs AP-1 and SP1 are strictly linked to G4s and suggest that G4s are exploited by cells to facilitate TF interaction with the DNA: this effect is reached by G4-mediated exposure of the binding region or altered DNA methylation state, as G4s were reported to prevent CpG island methylation, condition which is required for transcription initiation 3,14,27 . An alternative possibility is that TF binding to G4 regions stimulates G4 folding to maintain the underneath chromatin in a transcription permissive state.…”
Section: Analysis Of Accessible Chromatin Regions By Omni-atac-seqmentioning
confidence: 85%
“…Specific gene programs are activated in cells to maintain their diversity and identity. Chromatin organization and gene expression are modulated by a complex interplay between epigenetic marks (DNA methylation, histone modification, nucleosome positioning) and binding of core TFs to regulatory DNAs[1][2][3] . We hypothesized that G4s cooperated with TFs in the maintenance of cell-specific gene expression programs, contributing to the establishment of the transcriptome.…”
mentioning
confidence: 99%
“…The occurrence of GQs within the DNA is not random, and is notably conserved across species, thus supporting selective constraints and hence potential functional importance (Murat and Balasubramanian, 2014). Moreover, whereas transient GQs correlate with binding sites of chromatin remodeling-related transcription factors, genome-wide sites with more stable GQs have been implicated in replication stalling and inhibition of chromatin remodeling (Varizhuk et al, 2019), which support their involvement in regulation of higher order DNA organization. For example, GQ-ChIP-seq experiments revealed that most GQs tend to form within nucleosome-depleted regions with increased transcription activity (Hansel-Hertsch et al, 2016).…”
Section: Could Mtdna Packaging and Regulation Be Affected By G-quadrumentioning
confidence: 87%
“…For example, GQ-ChIP-seq experiments revealed that most GQs tend to form within nucleosome-depleted regions with increased transcription activity (Hansel-Hertsch et al, 2016). As GQ structures are mostly resolved by RecQ helicases (Mendoza et al, 2016;Sauer and Paeschke, 2017;Varizhuk et al, 2019), it is noteworthy that one such helicase, RecQ4, is transported into the mitochondria, interacts with DNA POLG and promotes mtDNA replication (Ding and Liu, 2015). Indeed, due to the asymmetric composition of nucleotides in the heavy (more guanine-rich) and light (more cytosine-rich) strands of mtDNA, the heavy mtDNA strand is prone to GQ formation.…”
Section: Could Mtdna Packaging and Regulation Be Affected By G-quadrumentioning
confidence: 99%
“…G-quadruplexes play a role in several key cellular processes, including gene transcription, chromatin epigenetics and DNA recombination. G-quadruplex DNA is found in key regulatory regions of the cell such as promoters of proto-oncogenes ( c-myc , bcl-2 and c-Kit ) [ 20 ]. Stabilization of the folded G-quadruplexes due to ligand interactions is proposed to inhibit the binding of transcription factors, leading to downstream silencing of oncogene expression [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%